THE EFFECT OF PRINCIPAL'S LEADERSHIP ON THE PERFORMANCE OF TEACHERS OF SOCIAL SCIENCE LESSONS IN SMPN PELALAWAN REGENCY - M. Yogi Riyantama Isjoni; Indra Primahardani; Asyrul Fikri (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2021)
The purpose of this study was to determine the effect of principal's leadership on social science teachers’ performance. The research was conducted in Pelalawan Regency taking Social Science teachers in Pelalawan Regency as the research subjects. The method used was a survey with quantitative techniques. The research sample was 150 Pelalawan Regency teachers selected using random sampling technique. The instrument used to collect data was a set of questionnaires used to quantify the school principal leadership level. Data of teachers’ performance were gathered from the teachers’ competency test (UKG) data. The results of this study indicate that there is a significant and positive influence of the principal's leadership on the performance of social science teachers at SMPN Pelalawan. The results of this study are expected to be useful for the improvement of the performance of school principals and social science teachers in Pelalawan Regency.